Synchronizing N Release from Organic Residues: Opportunities for Integrated Management of N - U. Singh; K.E. Giller; C.A. Palm; J.K. Ladha; H. Breman (The Scientific World Journal)
In intensive cropping systems, mineral nitrogen (N) fertilizers represent the largest component of the N cycle because the indigenous N supply is not adequate. The requirement for mineral fertilizer may be reduced with the use of organic nutrient sources. A more realistic use of organic matter, particularly in sub-Saharan Africa due to limited amounts and availability, is the combined use of organic nutrient sources and mineral fertilizers. The beneficial effects of integrated use of inorganic fertilizers and organic manures on improved nutrient recoveries, soil moisture retention, cation exchange capacity, and erosion control have been reported. However, there are as many reports indicating negligible benefits or even disadvantages of combining nutrient sources on crop production. This is not surprising given the combination of organic residue sources, soils, climatic, crops, and management factors that influence nutrient dynamics. The most widely accepted function of organic materials is improving the nutrient availability to crops by supplying N. The key to both improving efficiency of N use and reducing N losses is synchronization of N supply from soil, biological N2 fixation, organic residues, and inorganic fertilizers with the crop N demand. Organic materials are not magic; N losses also result from their use. Controlling N release from organic sources depends on their nutrient content and quality, soil properties, and the environmental and management factors. This paper will synthesize the information generated from integrated nutrient management trials in sub-Saharan Africa and the Philippines. Management strategies based on an organic resources database and a dynamic soil-crop simulation model are used to identify organic sources as N fertilizers or soil amendments. The decision support tools are also used to attain optimum synchrony between release from organic sources and soils with crop N demand.